2012
DOI: 10.1016/j.cmet.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a Physiologic Role for Acute Changes in CNS Insulin Action in the Rapid Regulation of Hepatic Glucose Production

Abstract: This review will discuss the physiologic relevance of data which suggest that CNS insulin action is required for the rapid suppression of hepatic glucose production. It will also review data from experiments on the conscious dog which show that while the canine brain can sense insulin, and thereby regulate hepatic glucoregulatory enzyme expression, CNS insulin action is not essential for the rapid suppression of glucose production caused by the hormone. Insulin’s direct hepatic effects are dominant, thus it ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…However, the second observation of enhanced whole-body insulin sensitivity after intranasal insulin application holds true. Of note, this effect is rapid and corresponds to the time course observed in rodents (3,6,14) but not in dogs (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the second observation of enhanced whole-body insulin sensitivity after intranasal insulin application holds true. Of note, this effect is rapid and corresponds to the time course observed in rodents (3,6,14) but not in dogs (11).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the action of insulin in the brain modulates insulin sensitivity in other organs such as liver (2,3,6,7), muscle (8), and adipose (1,9,10) tissue. However, at least for the liver, the relevance of this mechanism is still under debate (11,12).…”
mentioning
confidence: 99%
“…It has been reported that insulin still suppresses HGP partially even in mice with PI3K signal transduction inhibition in the liver [8,9]. Further, in an investigation of the changes in HGP after intravenous and intraportal insulin administration, it was shown that the differences in portal blood insulin level, that is, the direct insulin action on hepatocytes, do not necessarily correlate with the effect of insulin on HGP suppression [10].Indirect suppression of HGP by insulin is accomplished through the reduction of the release of glycerol and free fatty acids from the adipose tissue, which are the substrates and energy source of gluconeogenesis, and the decrease in the expression of hepatic gluconeogenic genes, including phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) [11]. Actually, in an investigation using dogs, maintenance of blood free fatty acid at a constant level by the intravenous administration of fat emulsion and heparin is reported to inhibit suppression of HGP during hyperinsulinemic-euglycemic clamp [12].…”
mentioning
confidence: 99%
“…Indirect suppression of HGP by insulin is accomplished through the reduction of the release of glycerol and free fatty acids from the adipose tissue, which are the substrates and energy source of gluconeogenesis, and the decrease in the expression of hepatic gluconeogenic genes, including phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) [11]. Actually, in an investigation using dogs, maintenance of blood free fatty acid at a constant level by the intravenous administration of fat emulsion and heparin is reported to inhibit suppression of HGP during hyperinsulinemic-euglycemic clamp [12].…”
mentioning
confidence: 99%
“…Suppression of lipolysis in adipose tissue by brain insulin signaling reduces the availability of gluconeogenic substrates for the liver, which will further decrease EGP (2). In contrast, studies in dogs did not support the concept of a physiological relevance of CNS insulin action for controlling EGP (7).…”
mentioning
confidence: 55%